Urejanje položaja žensk pri zaposlitvi v konvencijah in priporočilih Mednarodne organizacije dela v obdobju od 1919 do 1939 - Draksler, Urška (Delavci in delodajalci, 2019)
The purpose of the paper is to study the normative regulation of the position of women in employment within the International Labour Organization (ILO), from its inception (1919) to the outbreak of World War II (1939), and to contribute to the understanding of the setting of the relevant international labour standards in the light of the wider social context. Based on an outline of social circumstances and an analysis of the provisions of the adopted instruments, an assessment of the ILO's role in promoting gender equality in employment during its earliest period is given.
Keywords: delovno pravo; discrimination; diskriminacija; enakost spolov; gender equality; International Labour Organization (ILO); international labour standards; Mednarodna organizacija dela; mednarodne konvencije; women in employment; zaposlovanje; ženske